ODF1, sperm flagelar protein is expressed in kidney collecting ducts of rats. Issue 12 (December 2019) - Cabrillana, M.E.; Bocanegra, V.; Monclus, M.A.; Lancellotti, TE Saez; Simón, L.; Funes, A.K.; Colombo, R.; Ruiz Estrabón, M.; Vincenti, A.E.; Oliva, R.; Fornés, M.W.
Abstract: ODF1 has been described as an exclusively expressed testicular protein and is located in the outer dense fibers along the sperm tail. ODF1 has been involved in the sperm motility and in the development of the flagellum, but the function of ODF1 is not already clear. Other ODF proteins, such as ODF2 have been characterized in other tissues like the basal body of the kidney primary cilium, but so far only the mRNA of ODF1 has been described in other tissues. These observations let us to hypothesize that the expression of the protein ODF1 could not be limited to the testis. Therefore, in the present work we proposed to evaluate if the ODF1 protein could also be present in tissues other than the testis. Here we demonstrated through western blot, immunofluorescence, and RT-PCR techniques that the protein and mRNA of ODF1 have been identified in the rat kidney. Finally, the presence of ODF1 in kidney has also been confirmed through proteomic analysis using mass spectrometry. The results derived from these different complementary approaches indicate that, to our knowledge and for the first time, ODF1 is demonstrated to be present in an additional organ different to testis. This results raise new questions about potential other functions and locations of the ODF1 protein. Abstract : Cell biology; Proteins; Reproductive system; ODF1, Proteomic, Collecting duct